ISOTOPIC COMPOSITIONS OF C, N, O, MG, AND SI, TRACE ELEMENT ABUNDANCES, AND MORPHOLOGIES OF SINGLE CIRCUMSTELLAR GRAPHITE GRAINS IN FOUR DENSITY FRACTIONS FROM THE MURCHISON METEORITE - Hoppe P.; Amari S.; Zinner E.; Lewis R.S. (My University, 1995)
We report ion microprobe determinations of carbon, nitrogen, oxygen, magnesium-aluminum, and silicon isotopic compositions and trace element (H, N, O, Al, Si) concentrations of individual graphite grains (0.8-28 μm) from the Murchison CM2 chondrite. The analyzed grains exhibit large variations of their isotopic compositions: 12C13C ratios vary by a factor of 3500,14N15N ratios by a factor of 24, and16O18O ratios by a factor of 14. Most grains have isotopically light carbon and heavy nitrogen and excesses in 18O are positively correlated with excesses in 15N. According to their carbon isotopic composition and density we distinguish between four different groups of graphite grains. Many grains show large 26Mg excesses with inferred 26Al27Al ratios ranging up to 0.1. Highest26Al27Al ratios are found in grains with close-to-normal carbon isotopic composition. Most grains have normal Si but some have large silicon isotopic anomalies. One of these grains has isotopic characteristics similar to those of the rare SiC grains of type X.Nitrogen contents are roughly correlated with the contents of other trace elements. Grains with isotopically heavy carbon tend to have higher trace element contents than grains with isotopically light carbon. Most graphite grains (#92%) are round and dense. These grains either have smooth surfaces or appear to consist of dense aggregates of small scales. These surface morphologies are reflected in the internal structure of the grains. The morphology of graphite grains correlates with isotopic properties as only round grains have carbon isotopic anomalies, although small nitrogen anomalies are present in both round and nonround grains, and as morphologic subtypes of round grains are distributed differently over the range of 12C13C ratios. Combining both carbon isotopic compositions and morphologies we distinguish between six different groups of round graphite grains.The isotopic characteristics of most graphite grains strongly differ from those of circumstellar SiC, suggesting that these two types of circumstellar grains originate from distinct stellar sources. Wolf-Rayet stars and Type II supernovae seem to account for the isotopic properties of most (>60%) circumstellar graphite grains. The presence of Ne-E(L) with 20Ne22Ne < 0.087, the lower limit for He-shell Ne, and isotopically heavy carbon together with heavy nitrogen indicate that some grains (<1%) originate from novae. Evidence for an AGB star origin comes from Kr-S, but only few grains have isotopically heavy carbon and light nitrogen, expected from present stellar and nucleosynthetic models of these stars.